Constitutive reduction in the checkpoint inhibitor, CTLA-4, does not accelerate SLE in NZM 2328 mice. Issue 1 (19th February 2019) - Stohl, William; Yu, Ning; Chalmers, Samantha A; Putterman, Chaim; Jacob, Chaim O
Abstract : Background/objective: Treatment with immune checkpoint inhibitors (ICIs) in oncology patients is increasing. Although ICIs trigger rheumatic immune-related adverse events, development of SLE features has been rare. Whether long-term treatment with ICIs would promote SLE features remains unknown. To begin to address this, we generated SLE-prone NZM 2328 mice with lifelong reduction in CTLA-4 expression. Methods: Since CTLA-4-deficient ( Ctla4 − /− ) NZM mice developed a lethal lymphoproliferative disorder by 3–6 weeks of age, development of SLE in these mice could not be studied. Ctla4 haploinsufficient NZM. Ctla4 + / − mice were assessed in parallel with littermate female NZM. Ctla4 + / + mice. Evaluations included CTLA-4 expression and lymphocyte profiles, assessed by fluorescence-activated cell sorting; serological profiles, assessed by ELISA; renal immunopathology, assessed by histology and immunofluorescence; and clinical courses, assessed by mortality. Results: CTLA-4 expression was lower in NZM. Ctla4 + / − mice than in NZM. Ctla4 + / + mice. Spleen mononuclear cells, B cells, plasma cells, CD4 + cells, recently activated CD4 + cells and CD4 + T regulatory (Treg) cells were increased in NZM. Ctla4 + / − mice (p≤0.042). The serological profile, degree of renal immunopathology and mortality in NZM. Ctla4 + / − mice remained unaffected. Conclusion: Lifelong reduction in CTLA-4 expression in NZM mice neither accelerated nor aggravated SLE. Expansion in Treg cells may have played a protective role. Our observations raise the hope that long-term treatment of patients with SLE with an anti-CTLA-4 agent, should the need arise, would not adversely affect SLE disease activity.